Thick as thieves - Brown, Sandra, 1948- (Grand Central Publishing, 2020)
Arden Maxwell, the daughter of the man who vanished twenty years ago following his involvement in a heist gone wrong, returns to her family home near mysterious Caddo Lake to finally get answers to the questions that torment her about his disappearance, but little does she know, two of her father's co-conspirators -- a war hero and a corrupt district attorney -- are watching her every move.